2016
DOI: 10.4314/evj.v20i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of camel tuberculosis and associated risk factors in camels slaughtered at Akaki Abattoir, Ethiopia

Abstract: A cross sectional abattoir based study was conducted from February 2014 to October, 2015 on camels slaughtered at Akaki municipality abattoir to determine the prevalence of Tuberculosis in camels and assess the association of risk factors with the prevalence of Tuberculosis in camels using single intra-dermal comparative cervical tuberculin (SICCT). Of the total of 387 camels investigated, overall camel tuberculosis prevalence of 9.82% (95% CI: 6.84%-12.8%) at a cut off value ≥ 4mm and prevalence of 17.05% (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
4
2
Order By: Relevance
“…Breeds considered in our study were Somali, Rendile and Turkana which may be different genetically from those in Ethiopia and Eritrea; with regard to sex, our study considered lactating camels only, which have a unique physiological and immunity status, while similar studies looked at both male and female camels. The overall proportion that showed a positive reaction to M. avium PPD was much greater in our study compared to estimates from similar studies (Gumi, Schelling, Berg, et al, 2012; Gumi, Schelling, Firdessa, et al, 2012; Jibril, Mamo, Hanur, Zewude, & Ameni, 2016; Lamuka et al, 2018). In all of these studies, despite the low sensitivity of tuberculin skin testing, it was concluded that the camels were infected with mycobacteria without confirmatory isolation of the causative agent (Jibril et al, 2016).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Breeds considered in our study were Somali, Rendile and Turkana which may be different genetically from those in Ethiopia and Eritrea; with regard to sex, our study considered lactating camels only, which have a unique physiological and immunity status, while similar studies looked at both male and female camels. The overall proportion that showed a positive reaction to M. avium PPD was much greater in our study compared to estimates from similar studies (Gumi, Schelling, Berg, et al, 2012; Gumi, Schelling, Firdessa, et al, 2012; Jibril, Mamo, Hanur, Zewude, & Ameni, 2016; Lamuka et al, 2018). In all of these studies, despite the low sensitivity of tuberculin skin testing, it was concluded that the camels were infected with mycobacteria without confirmatory isolation of the causative agent (Jibril et al, 2016).…”
Section: Discussioncontrasting
confidence: 66%
“…The overall proportion that showed a positive reaction to M. avium PPD was much greater in our study compared to estimates from similar studies (Gumi, Schelling, Berg, et al, 2012; Gumi, Schelling, Firdessa, et al, 2012; Jibril, Mamo, Hanur, Zewude, & Ameni, 2016; Lamuka et al, 2018). In all of these studies, despite the low sensitivity of tuberculin skin testing, it was concluded that the camels were infected with mycobacteria without confirmatory isolation of the causative agent (Jibril et al, 2016). Currently, the screening tests for mycobacteria recommended by the OIE are specifically for the detection of M. bovis and are not appropriate for the detection of other mycobacteria.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…[22], who reported 19.56%, Jibril et al . [23], who reported 9.82%, and Ahmad et al . [24], who reported 33.5%.…”
Section: Discussionmentioning
confidence: 99%
“…There is little published information on the epidemiology of TB specifically relating to camelids (Rhodes et al 2015). However, recently, few studies have been conducted on the epidemiology of tuberculosis in camels (Beye et al 2014; Gumi et al 2012; Jibril et al 2016; Kassaye et al 2013; Mamo et al 2009, 2011; Zerom et al 2013). Prevalence data on camel tuberculosis reported in Ethiopia showed lesion prevalence of 5.07 and 10.04% by Mamo et al (2009, 2011); and 4.52% by (Kassaye et al 2013).…”
Section: Introductionmentioning
confidence: 99%